2006
DOI: 10.1111/j.1365-2672.2006.02995.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and description of transmission routes for Campylobacter on broiler farms by amplified-fragment length polymorphism

Abstract: Aims:  To investigate the genetic diversity of Campylobacter in broilers and in the environment of broiler farms, to compare the genetic profiles and describe critical factors for transmission to broilers. Methods and Results:  Flocks at three of four investigated farms became colonized with Campylobacter. The total proportion of Campylobacter‐positive samples at different farms varied from 20% to 42%. The farm with the poorest biosecurity routines had broilers that became infected earliest, the highest propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
56
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 35 publications
6
56
0
Order By: Relevance
“…According to EFSA (2010a), the prevalence in the EU of Campylobacter-contaminated broiler carcasses, in 2008, was reported as 75.8% and varied from 4.9% to 100.0% among the EU MSs. That prevalence is higher than the respective prevalence for broiler batches, which come into accordance with the results of other studies (Hue et al, 2011;Powell et al, 2012;Chokboonmongkol et al, 2013), assuming that cross-contamination from positive batches to negative batches does occur during the slaughtering process and associated carcass preparation (Jørgensen et al 2002;Johannessen et al 2007;EFSA, 2010a;Hue O. et al, 2011) through contamination of the slaughterhouse environment (Johnsen et al 2006). The counts of Campylobacter bacteria on broiler carcasses varied widely also between countries, which might be due to differences in slaughterhouse hygiene and processing practices Sampers et al, 2008;EFSA, 2010a).…”
Section: Broiler Slaughterhouses -Carcassessupporting
confidence: 79%
“…According to EFSA (2010a), the prevalence in the EU of Campylobacter-contaminated broiler carcasses, in 2008, was reported as 75.8% and varied from 4.9% to 100.0% among the EU MSs. That prevalence is higher than the respective prevalence for broiler batches, which come into accordance with the results of other studies (Hue et al, 2011;Powell et al, 2012;Chokboonmongkol et al, 2013), assuming that cross-contamination from positive batches to negative batches does occur during the slaughtering process and associated carcass preparation (Jørgensen et al 2002;Johannessen et al 2007;EFSA, 2010a;Hue O. et al, 2011) through contamination of the slaughterhouse environment (Johnsen et al 2006). The counts of Campylobacter bacteria on broiler carcasses varied widely also between countries, which might be due to differences in slaughterhouse hygiene and processing practices Sampers et al, 2008;EFSA, 2010a).…”
Section: Broiler Slaughterhouses -Carcassessupporting
confidence: 79%
“…Farm-level epidemiological survey-based studies have identified a number of important risk factors for infection of broiler flocks (4,15,22,24) and in recent systematic reviews (1; http://www.foodbase.org.uk/results.php?f_category_idϭ &f_report%20idϭ384) of available literature, the most important risk factors identified included the age of the flock, the use of staggered slaughter, the presence of multiple broiler houses, farmworkers, and other livestock on the farm. Molecular epidemiological investigations have provided supporting evidence for the role of farm surrounds and onfarm puddles (5,20), flies (16), transport crates (17), and broiler house water systems (30) as sources. However, the direction of this environmental contamination is uncertain and may be both from and into the poultry house.…”
mentioning
confidence: 99%
“…This investigation has also provided evidence that campylobacter contamination of the farmer's boots provided the route of transmission from the cattle in the adjacent field to the poultry farm environment, probably causing colonization in houses on adjacent farm B first and then leading to colonization of the flock on farm A. Campylobacters recovered from farmers' boots were identified in a recent study as a likely source of flock infection (22), and a report from the Food Standards Agency entitled Evidence for the Effectiveness of Bio- (1), clearly indicates that farmers are the major vehicle for tracking campylobacters into poultry houses. There is also a possible role for the feed truck in transmission as a P1.T1-positive signal was recovered from a wheel well, but there were many other strains also present and a clear relationship to the poultry-colonizing strain could not be confirmed.…”
Section: Discussionmentioning
confidence: 99%